상경부교감신경절블록이 백서의 국소 뇌허혈/재관류로 인한 뇌 손상에 미치는 영향 - 이애령; Ae Ryoung Lee; 윤미옥; Mi Ok Yoon; 김현혜; Hyun Hae Kim; 최재문; Jae Moon Choi; 전혜영; Hae Yuong Jeon; 신진우; Jin Woo Shin; et al. (The Korean journal of pain, 2007)
Background: Cerebral blood vessels are innervated by sympathetic nerves that originate in the superior cervical ganglia (SCG). This study was conducted to determine the effect of an SCG block on brain injury caused by focal cerebral ischemia/reperfusion in a rat model. Methods: Male Sprague-Dawley rats (270-320 g) were randomly assigned to one of three groups (lidocaine, ropivacaine, and control). After brain injury induced by middle cerebral artery (MCA) occlusion/reperfusion, the animals were administered an SCG bloc that consisted of $30μl$ of 2% lidocaine or 0.75% ropivacaine, with the exception of animals in the control group, which received no treatment. Twenty four hours after brain injury was induced, neurologic scores were assessed and brain samples were collected. The infarct and edema ratios were measured, and DNA fragmented cells were counted in the frontoparietal cortex and the caudoputamen. Results: No significant differences in neurologic scores or edema ratios were observed among the three groups. However, the infarct ratio was significantly lower in the ropivacaine group than in the control group (P < 0.05), and the number of necrotic cells in the caudoputamen of the ropivacaine group was significantly lower than in the control group (P < 0.01). Additionally, the number of necrotic and apoptotic cells in theropivacaine group were significantly lower than inthe control group in both the caudoputamen and the frontoparietal cortex (P < 0.05). Conclusions: Brain injury induced by focal cerebral ischemia/reperfusion was reduced by an SCG block using local anesthetics. This finding suggests that a cervical sympathetic block could be considered as another treatment option for the treatment of cerebral vascular diseases.